2012
DOI: 10.1152/ajprenal.00343.2011
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol induces nongenomic effects in renal intercalated cells through G protein-coupled estrogen receptor 1

Abstract: Hofmeister MV, Damkier HH, Christensen BM, Olde B, LeebLundberg LM, Fenton RA, Praetorius HA, Praetorius J. 17␤-Estradiol induces nongenomic effects in renal intercalated cells through G protein-coupled estrogen receptor 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…Although, not all estrogen-mediated renoprotective effects are tractable to any of the known estrogen receptors (ERα, ERβ or GPER), as demonstrated by the work of Anderson and colleagues using a renal injury model of cardiac arrest and resuscitation [Hutchens et al, 2012;Hutchens et al, 2014]. GPER is well expressed in the kidney, albeit with differences regarding its subcellular distribution, which may in part be due to differences in methodological approaches in measuring its expression and activity [Cheng et al, 2011;Hofmeister et al, 2012;Cheng et al, 2014]. The selective GPER agonist, G1, estradiol-17β (E2), and the ER antagonist (and GPER agonist) ICI 182,780 induce intracellular calcium signals in microdissected renal tubule segments and isolated intercalated cells not detected in explants and cells isolated from GPER-1-deleted mice [Hofmeister et al, 2012].…”
Section: Renoprotective Effects and Absence Of Aldosterone Binding Acmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, not all estrogen-mediated renoprotective effects are tractable to any of the known estrogen receptors (ERα, ERβ or GPER), as demonstrated by the work of Anderson and colleagues using a renal injury model of cardiac arrest and resuscitation [Hutchens et al, 2012;Hutchens et al, 2014]. GPER is well expressed in the kidney, albeit with differences regarding its subcellular distribution, which may in part be due to differences in methodological approaches in measuring its expression and activity [Cheng et al, 2011;Hofmeister et al, 2012;Cheng et al, 2014]. The selective GPER agonist, G1, estradiol-17β (E2), and the ER antagonist (and GPER agonist) ICI 182,780 induce intracellular calcium signals in microdissected renal tubule segments and isolated intercalated cells not detected in explants and cells isolated from GPER-1-deleted mice [Hofmeister et al, 2012].…”
Section: Renoprotective Effects and Absence Of Aldosterone Binding Acmentioning
confidence: 99%
“…GPER is well expressed in the kidney, albeit with differences regarding its subcellular distribution, which may in part be due to differences in methodological approaches in measuring its expression and activity [Cheng et al, 2011;Hofmeister et al, 2012;Cheng et al, 2014]. The selective GPER agonist, G1, estradiol-17β (E2), and the ER antagonist (and GPER agonist) ICI 182,780 induce intracellular calcium signals in microdissected renal tubule segments and isolated intercalated cells not detected in explants and cells isolated from GPER-1-deleted mice [Hofmeister et al, 2012]. Moreover, GPER colocalizes with megalin in renal proximal tubules and G1 ameliorates saltinduced renal injury in female mRen2.Lewis mice independently of changes in systolic blood pressure .…”
Section: Renoprotective Effects and Absence Of Aldosterone Binding Acmentioning
confidence: 99%
“…Estrogen and G-1 as well as the SERD ICI 182,780 (fulvestrant), an ER antagonist, were shown to stimulate rapid calcium signaling and H + -ATPase activity in renal tubules and isolated intercalating cells (Hofmeister et al, 2012). All three ligands were without effect in tubules and cells isolated from GPER knockout mice, once again demonstrating the critical role of GPER in these activities.…”
mentioning
confidence: 95%
“…16 GPER-1 is highly expressed in kidney tissues albeit with differences regarding its subcellular distribution, which may in part be due to differences in methodological approaches in measuring its expression and activity. [17][18][19][20][21] Recently, Filardo and coworkers evaluated the topographic mapping of GPER-1 expression in renal tubules using dual immunostaining of the receptors and specific markers for distinct tubules in tissue section. 22 The results revealed that GPER-1 immunoreactivity is mainly localized in the distal convoluted tubules and the loop of Henle, and to a lower level in the proximal convoluted tubules.…”
mentioning
confidence: 99%
“…The specific GPER-1 agonist, G1, 15 estradiol-17β (E2), and ICI 182,780 (the ER antagonist and GPER-1 agonist) 12 have been reported to increase acute Ca 2+ concentration and H + -ATPase activity intracellular calcium signals in microdissected renal tubule segments and isolated intercalated cells but not in similar explants and cell cultures isolated from GPER-1-deleted mice, suggesting a role for GPER-1 in regulating Na + and Ca 2+ reabsorption in renal tubules and subsequently affecting fluid retention. 21 Prior studies revealed that G1 and estradiol-17β induce vasodilation in female mouse, pig and rat and vasoconstriction in male rat. 23 A recent study demonstrated that GPER-1 exerts beneficial effects on preventing excessive mesangial matrix production and modulates mesangial cell migration.…”
mentioning
confidence: 99%